Psychiatric consequences and issues of long COVID on patients with prior psychiatric comorbidities: a scoping review - Hovagemyan, Francesca; Dugerdil, Adeline; Braggion, Axelle; Mallet, Luc; Flahault, Antoine (Frontiers in Psychiatry, 2023)
SARS-CoV-2 is a growing field of research and mental health in long COVID is one of its interesting domains. This scoping review aims at studying the outcomes of mental health in patients already known for psychiatric illness. This was done by researching the literature in two databases (Embase and PubMed) for articles studying mental health consequences of long COVID in patients already known for psychiatric history. Eleven studies were included. 6/11 studies found an effect of long COVID, with varying severity of outcomes studied, with either a worsening in length or severity. 4/11 did not find any correlation between worsening symptoms and psychiatric history. The methods for assessing which psychiatric symptoms to include and how to determine prior history were heterogeneous, making direct comparison sometimes difficult. The data seem to show worse effects of long COVID on mental health of patients with prior mental illness, with limitations regarding the heterogeneity of the studies’ designs and focuses. It also highlights how neglected this population of patients is in the current state of research.